2022
DOI: 10.1177/09612033221132484
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box protein 1 (HMGB1) serum and urinary levels and gene polymorphism in Egyptian patients with systemic lupus erythematosus: A possible relation to lupus nephritis

Abstract: Objective The aim of this study was to evaluate the effects of the high mobility group box protein 1 (HMGB1) serum and urinary levels and gene polymorphisms on systemic lupus erythematosus (SLE) development and investigate their link to lupus nephritis (LN). Methods We enrolled 120 Egyptian SLE patients and 120 healthy controls. Thorough medical and clinical evaluation were carried out, and SLE disease activity index (SLEDAI) was assessed. Lupus patients were divided into two groups according to the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…However, these biomarkers are imprecise and lack a robust model to differentiate between proliferative and non-proliferative renal lesions [23,39,40]. Recent research has also identified other promising serum and urinary biomarkers such as NGAL (neutrophil gelatinase-associated lipocalin), MCP-1 (monocyte chemoattractant protein), TWEAK (tumor necrosis factor-like weak inducer of apoptosis), VCAM (vascular cell adhesion molecule), adiponectin, hemopexin, kidney injury molecule-1 and HMGB1 (high mobility group box protein 1) [23,41]. However, these biomarkers are still experimental, and any future potential use will likely be hindered by the cost of these tests as well as the lack of availability, especially in low-resource countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, these biomarkers are imprecise and lack a robust model to differentiate between proliferative and non-proliferative renal lesions [23,39,40]. Recent research has also identified other promising serum and urinary biomarkers such as NGAL (neutrophil gelatinase-associated lipocalin), MCP-1 (monocyte chemoattractant protein), TWEAK (tumor necrosis factor-like weak inducer of apoptosis), VCAM (vascular cell adhesion molecule), adiponectin, hemopexin, kidney injury molecule-1 and HMGB1 (high mobility group box protein 1) [23,41]. However, these biomarkers are still experimental, and any future potential use will likely be hindered by the cost of these tests as well as the lack of availability, especially in low-resource countries.…”
Section: Discussionmentioning
confidence: 99%